Gastroesophageal Reflux (GER) - Rahayu Sa'at (Indonesian Pediatric Society, 1984)
Gastroesophageal Reflux ( GER ) is one of the most frequent congenital gastrointestinal tract anomalies. The anatomy and physiology of lower esophageal sphincter (LES) is adapted to prevent reflux in normal infants and children. Vomiting is the most common symptom with following complications: failure to thrive, aspiration penumonia, esophagitis and strictures. GER is thought to be associated with other diseases such as Sandifer syndrome, rumination and sudden infant death syndrome (SIDS). Upper gastrointestinal series ( UGI series) is the most common and simple diagnostic test in GER. Management should start with medical therapy such as positional therapy, dietary consideration, and drugs. For non responders, surgical intervention must be considered. In the absence of therapy approximately 60 - 65% of cases will be free of symptoms up till 2 years of age. About 5% of cases will die because of pneumonia and severe malnutrition.